2022
DOI: 10.1002/pul2.12106
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of risk assessment in PAH: Expert center APRN recommendations

Abstract: Performing longitudinal and consistent risk assessments for patients with pulmonary arterial hypertension (PAH) is important to help guide treatment decisions to achieve early on and maintain a low‐risk status and improve patient morbidity and mortality. Clinical gestalt or expert perception alone may over or underestimate a patient's risk status. Indeed, regular and continued use of validated risk assessment tools more accurately predict patients' survival. Effective PAH risk assessments are often underutiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 48 publications
(86 reference statements)
0
12
0
Order By: Relevance
“… 26 In another study based on real-world experience addressing barriers for incorporation of risk assessment into clinical practice, it was found that lack of time among clinicians prevented regular use of risk assessment tools, and technology-based solutions as time-saving tools were recommended to overcome the barrier of suboptimal use of risk assessment. 27 The utilization of risk assessment in the clinics has been influenced by the presence of several contemporary risk stratification models advocating the use of different numbers and combinations of prognostic parameters, 21 , 26 as well as the lack of a time-saving and comprehensive risk calculator. We therefore aimed to establish and introduce an independent html-based webpage to facilitate risk score calculation in PAH and thereby evaluate and provide insight into various ESC/ERS risk assessment models with respect the number of included parameters, during baseline and follow-ups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 26 In another study based on real-world experience addressing barriers for incorporation of risk assessment into clinical practice, it was found that lack of time among clinicians prevented regular use of risk assessment tools, and technology-based solutions as time-saving tools were recommended to overcome the barrier of suboptimal use of risk assessment. 27 The utilization of risk assessment in the clinics has been influenced by the presence of several contemporary risk stratification models advocating the use of different numbers and combinations of prognostic parameters, 21 , 26 as well as the lack of a time-saving and comprehensive risk calculator. We therefore aimed to establish and introduce an independent html-based webpage to facilitate risk score calculation in PAH and thereby evaluate and provide insight into various ESC/ERS risk assessment models with respect the number of included parameters, during baseline and follow-ups.…”
Section: Discussionmentioning
confidence: 99%
“…During assessment of patients with PAH, expert perception or clinical gestalt alone may overestimate or underestimate the risk status. 26 , 27 In a study based on real-world experience addressing barriers for incorporation of risk assessment into clinical practice, it was found that risk assessment in PAH is often underutilized although many clinicians attest to the use of validated risk stratification tools. Also, lack of time among clinicians was found to prevent regular use of risk assessment tools.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the use of risk stratification is not restricted to estimate risk at diagnosis or initiation of therapy. Also serial risk stratification every 3-6 months is proposed in order to use follow-up risk estimates to evaluate treatment response and to identify the need to escalate therapy (47). Recent reports show that risk stratifications may have a better discrimination of outcome at first follow-up RHC compared to baseline (48), and that changes in risk status are predictive of survival (49) Nearly all studies included in this systematic review were judged to have a high ROB based on their analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the studies by Wilson et al 1 "Current clinical utilization of risk assessment tools in pulmonary arterial hypertension: a descriptive survey of facilitation strategies, patterns, and barriers to use in the United States," and "Clinical application of risk assessment in PAH: Expert center APRN recommendations," 2 as well as the recent publication by Sahay et al 3 "Utilization of risk assessment tools in management of PAH: A PAH provider survey"; all published in previous issues of Pulmonary Circulation. We acknowledge the authors for their contributions on assessing the clinical utilization of risk assessment in pulmonary arterial hypertension (PAH), 1,3 identifying potential major barriers impacting clinical underutilization and presenting recommendations to overcome these barriers.…”
Section: Dear Editormentioning
confidence: 99%